Forest land management and the role of ecological silviculture on the sustainability of Greek forests - Tsakaldimi, Marianthi; Ganatsas, Petros (Journal of Degraded and Mining Lands Management, 2024)
One of the challenges faced by current forestry practice is how to effectively respond to the great environmental and global changes to achieve biodiversity conservation and the demands for timber and other non-wood forest products. Worldwide forestry suggests that the approach of ecological silviculture can provide efficient tools for facing these challenges. The applied forest land management during the last seven decades in Greece relies on the principles of sustainability set by ecological silviculture through time. Greek silviculturists adopted these principles many years ago by setting the following priorities and perspectives for applied Greek forestry: the protection of all Greek forests, the systematic rehabilitation of degraded forests (e.g., conversion of coppices to high forest), the promotion of tree species mixture, the improvement of the horizontal and vertical structure of all forest ecosystems, the exclusive use of species natural regeneration, the application of selective felling prohibiting any of clear-cutting, the extensive use of low impact harvesting practices, the retention of a small number of old trees for promoting biodiversity, the protection of all rare and endangered flora and fauna species, and establishment forest protected areas. In this study, three modern indicators were used to evaluate the results of the above silvicultural ecological approach to Greek forests after a period of seven years of forestry practice based on these principles.